The influence of thyroid hormone replacement on endometrial receptivity in infertile women - Khan, Iftesham; Sharma, Rupali; Singhal, Sunita; Singh, Anjali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Infertility affects 10–15% of couples worldwide, with thyroid dysfunction-especially hypothyroidism-recognized as a significant modifiable contributor. Thyroid hormones influence reproductive health by regulating ovulation, endometrial receptivity, and hormonal balance. This study aimed to assess the impact of thyroid hormone replacement (levothyroxine) on endometrial receptivity and conception outcomes in infertile women diagnosed with clinical or subclinical hypothyroidism. Methods: Conducted as a prospective observational study at GS Medical College and Hospital, Hapur (2023–2025), it included 60 women aged 21–40 years with clinical or subclinical hypothyroidism. Participants underwent detailed clinical assessments, hormonal profiling (TSH, T3, T4, prolactin), and pelvic ultrasonography. Levothyroxine therapy was initiated and adjusted over a 3–12-month follow-up. Outcomes measured included hormonal normalization and pregnancy (via urine pregnancy test). Result: Results showed a significant decline in TSH (12.07±8.4 to 6.26±2.96 mIU/l) and prolactin (13.9±5.67 to 10.9±3.96 ng/ml) levels post-treatment (p<0.001). Conception occurred in 61.5% of women with subclinical and 57.1% with clinical hypothyroidism, with no significant difference (p=0.956). Maximum conception was noted in women with mid-range TSH (6.5–10 mIU/l). Levothyroxine therapy improved hormonal profiles and supported conception across both groups. Conclusion: The study concludes that early diagnosis and treatment of even mild hypothyroidism can enhance fertility outcomes, underscoring the importance of routine thyroid screening in infertility evaluations.